Boys will always be boys? The impacts of gender-based Affirmative Action and Role Models on competitiveness in the lab - Hare, Aimee Elizabeth (School of Economics, 2019)
Gender differences in labour market outcomes are pervasive in current society. Competitiveness is viewed as a possible factor contributing to the favourable labour market outcomes for men, with the stylised fact being that men are more competitive than women on average. In this study, we experimentally investigate whether institutional structures (gender-based Affirmative Action and Role Models) mitigate the gender differences in competitiveness. Although Affirmative Action has been explored in the literature, the longer-term implications of the preferential treatment creating role model representation have not been examined. Consistent with the literature, we find men have a higher preference for a competitive environment compared with women in our sample. However, there are no significant impacts of the gender based institutional structures on the choice to compete in our experiment. When analysing the responsiveness of performance to a competitive environment and the associated beliefs, we see the female role model treatment encourages a competitive spirit in everyone, whereas the Affirmative Action treatment has a negative effect on the competitive performance of African men. In this experiment, gender-based institutions therefore either have unexpected effects of encouraging competitiveness in all participants, or inadvertently reinforce competitiveness gaps across other dimensions of identity, such as population-group. One therefore needs to be considerate of other dimensions of identity in addition to gender when devising preferential treatment policies, and the resulting role model representation, in practice. Changes in beliefs can only partially be exercised as an explanatory channel for these effects.